Association between the newly proposed dietary index for gut microbiota and thyroid function: NHANES 2007–2012 - Peng, Ke; Guo, Hanjie; Zhang, Zhiqiang; Xiao, Weidong (Frontiers in Nutrition, 2025)
AimsDiet-gut-thyroid axis has attracted increasing interest. The dietary index for gut microbiota (DI-GM) is a recently introduced measure of diet quality that represents gut microbiota diversity. However, its relationship with thyroid function has not been investigated. This study aimed to examine the unexplored relationship between DI-GM and thyroid function.MethodsThis cross-sectional study analyzed data from 6,126 participants aged ≥20 years in the National Health and Nutrition Examination Survey (NHANES). Linear regression models, smoothed curve fitting, and subgroup analyses were used to examine the relationship between DI-GM and thyroid function.ResultsAfter controlling for all covariates, higher DI-GM scores were significantly associated with lower levels of free triiodothyronine (FT3) (β = −0.043, 95% CI = −0.077, −0.010, P for trend = 0.010), free thyroxine (FT4) (β = −0.011, 95% CI = −0.021, −0.002, P for trend = 0.027), and total thyroxine (TT4) (β = −0.127, 95% CI = −0.237, −0.017, P for trend = 0.024). Smooth curve fitting analysis confirmed a linear relationship between DI-GM and FT3, FT4, and TT4 levels. Furthermore, subgroup analyses indicated that age may influence the negative correlation between DI-GM and FT4 levels, with participants aged < 40 years exhibiting a more pronounced decrease in FT4 levels (β = −0.090, 95% CI: −0.140, −0.041). Smoking status may modify the relationship between DI-GM and thyroid hormone levels, showing negative correlations for FT3 levels only in never smokers (β = −0.073, 95% CI = −0.114, −0.032) and for TT4 levels only in former smokers (β = −0.316, 95% CI = −0.511, −0.122). Notably, thyroglobulin antibodies levels exhibited opposing directional effects between never smokers (negative) and former/current smokers (positive).ConclusionHigher DI-GM scores were negatively correlated with lower FT3, FT4, and TT4 levels, with age and smoking status serving as key factors influencing this association.